Book review: Brown, B. (2015). Daring greatly: How the courage to be vulnerable transforms the way we live, love, parent, and lead. Penguin books, ISBN 9781592408412 - Chris Walter (Scottish Journal of Residential Child Care)
I first came across Dr. Brené Brown and her research when a friend recommended that I watch her 2011 TED talk on YouTube entitled 'The power of vulnerability'. This video has now been watched by more than 4.5 million people and so it's likely that some people reading this review will have seen it. When something has become so popular there is the danger that it will become commodified and turn into a brand: a quick search on Google reveals that Brené Brown now has published more books, has her own website and other merchandising. However, the very popularity of the book should not detract from some valuable messages of her research. Not everyone will feel comfortable with her writing style, replete with homespun anecdotes – but she has some important insights about the challenges of bringing our self into our work. Whilst the book is not specifically aimed at those working with troubled children and young people, its insights are highly relevant in my opinion.